A grammar of New Testament Greek - Whitacre, Rodney A. (Eerdmans language resources, 2021)
Introduction to Greek writing, pronunciation, and punctuation -- Basic features of Ancient Greek -- Morphology of nominal forms -- Morphology of verbal form -- Greek syntax -- Appendix 1: Rules for accenting -- Appendix 2: Words distinguished by their accents and breathing marks -- Appendix 3: Common suffixes -- Appendix 4: Paradigms for reference -- Appendix 5: Summary of selected syntax topics -- Appendix 6: Simple overview of English grammar essentials -- Appendix 7: Suggestions for approaching a sentence in Greek -- Appendix 8: Principal parts of common Greek verbs -- Glossary of grammatical terms -- Bibliography -- Index of subjects -- Index of scripture -- Index of Greek words.